Homeowner subsidies and suburban living: Empirical evidence from a subsidy repeal - Alexander Daminger (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
This paper documents effects of a homeownership subsidy's full repeal on the urban-rural residential location choice. First, I document the distribution of population across space for German labor market regions, using official NUTS-3 level population statistics. These labor market regions usually consist of a city (the urban core) and adjacent counties (the urban hinterlands) connected by commuter flows. Second, using IV-estimations in Difference-in-Differences and Triple-Differences frameworks, I exploit the 2005 repeal of Germany's lump-sum direct homeownership subsidy "Eigenheimzulage" on changes in this distribution across space. The results indicate that repealing subsidies to homeownership reverses subsidy-induced population flows to the periphery and thus makes regions re-urbanize. Cities' population gains derive in large parts from families with children and young residents of "building age", that are no longer able to become homeowners outside the city gates without the subsidy's support.
Keywords: H24; H30; H71; R23; R28; 330; homeownership; housing subsidies; residential location choice; suburbanization